Yeast Biotechnology - Ronnie G. Willaert (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Yeasts are truly fascinating microorganisms. Due to their diverse and dynamic activities, they have been used for the production of many interesting products, such as beer, wine, bread, biofuels, and biopharmaceuticals. Saccharomyces cerevisiae (brewers' or bakers' yeast) is the yeast species that is surely the most exploited by man. Saccharomyces is a top choice organism for industrial applications, although its use for producing beer dates back to at least the 6th millennium BC. Bakers' yeast has been a cornerstone of modern biotechnology, enabling the development of efficient production processes. Today, diverse yeast species are explored for industrial applications. This Special Issue is focused on some recent developments of yeast biotechnology, i.e., bioethanol, wine and beer, and enzyme production. Additionally, the new field of yeast nanobiotechnology is introduced and reviewed.